Addressing Student Tardiness Through a Strategic Reward System: A Study Among Grade 12 Students - Montederamos, Charis Eime A. (RIRAI Publisher, 2024)
This action research explored the effectiveness of a Strategic Reward System (SRS) in reducing student tardiness among Grade 12 students at Libertad National High School. The main objective was to determine whether implementing a structured reward system could significantly decrease instances of tardiness and enhance punctuality. The study employed a pre- and post-observation design, collecting data from student attendance records before and after the implementation of a lottery-based SRS. The intervention provided tangible incentives for on-time attendance, and the results were analyzed using a Mean Percentage Score and a T-test to assess the significance of changes in student behavior. The findings revealed a notable reduction in student tardiness, with statistical analysis confirming a significant difference between pre-and post-intervention data. The results align with existing literature on the positive impact of reward-based strategies in educational settings. It is suggested that schools adopt a structured reward system as part of their behavior management policy to foster a culture of punctuality and enhance student engagement. Future research should expand on these findings by exploring the application of reward systems across diverse educational contexts and incorporating gamified elements to sustain student motivation.